Bromine-induced facile synthesis of butenolides and spirobutenolides from sterically congested tetrasubstituted dialkyl alkylidene succinates - Patel, Ramesh M.; N. P. Argade (Synthesis-Stuttgart, 2010)
Starting from sterically congested tetrasubstituted dialkyl alkylidene succinates, facile general approach to several dialkyl substituted butenolides and spirobutenolides with the generation of quaternary carbon center has been demonstrated via bromine-induced dealkylative regioselective intramolecular cyclization and dehydrobromination pathway. The mechanistic aspects involved in the formation of butenolides have been also described in brief.
Keywords: alkylidene succinates; bromine; butenolides; intramolecular cyclizations; spirobutenolides

Biology-orientated synthesis of putrescine bisamides gigantamide A, dasyclamide, and cucullamide - Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2013)
Starting from putrescine and the requisite carboxylic acids, first syntheses of bioactive natural products gigantamide A, dasyclamide, and cucullamide were accomplished in very good overall yields using an appropriate sequence of dehydrative coupling reactions. The syntheses of the corresponding dehomo analogues of these natural products are also described. Regioselective diisobutylaluminum hydride reduction of an unhindered carbonyl group in citraconimide is the key step.
Keywords: dehydrative coupling reactions; diamines; natural and unnatural bisamides; regioselective reduction; synthesis

Base-stimulated 1,2-, 1,4-, and 1,6-eliminations in suitably substituted alkylidenesuccinates leading to natural and unnatural conjugated alkenyl(methyl)maleic anhydrides - Deore, Prashant S.; N. P. Argade (Journal of Organic Chemistry, 2014)
With dimethyl maleate as the starting material, facile stereoselective syntheses of natural and unnatural conjugated alkenyl(methyl)maleic anhydrides have been described. The key reactions were base-endorsed novel 1,2-, 1,4-, and 1,6-eliminations in the corresponding alkylidenesuccinate derivatives. The 1,2-eliminations in cyclic carbonate and sulfite by regioselective abstraction of methine protons with the respective release of CO2 and SO2 provided a conjugated ketone product. The characteristic 1,4- and 1,6-elimination reactions with respective release of acetone and mesylate furnished the corresponding unsaturated alcohols. The obtained allylic alcohols were transformed into conjugated alkenyl(methyl)maleic anhydrides via oxidation followed by a Horner-Wadsworth-Emmons reaction pathway in very good yields. The mechanistic aspects involved in these significant elimination reactions have also been described in brief.

Biomimetic synthesis of phaitanthrin e involving a fragmentation of sp(3) carbon-carbon bond: synthesis and rearrangement of phaitanthrin D to phaitanthrin E - Vaidya, Sagar D.; N. P. Argade (Organic Letters, 2015)
A biogenetic type total synthesis of alkaloids phaitanthrin D and phaitanthrin E has been described. The Csp(3)-Csp(3) bond cleavage with the release of several heteroatoms bearing unexpected leaving groups in intramolecular substitution reactions on an iminium double bond in the quinazolinones has been demonstrated using HMDS/ZnCl2 or NaHMDS. The mechanistic aspects have been supported by isolation and characterization of appropriate intermediates.

Biomimetic collective total synthesis of bioactive carbazole alkaloids indizoline, mafaicheenamine A, claulamine A, claulansine A, and the proposed claulamine E - Markad, Shivaji B.; N. P. Argade (Journal of Organic Chemistry, 2016)
The common precursor 1-methoxy-2-prenyl-3-carbomethoxycarbazole was synthesized from dimethyl indolylmethylenesuccinate in four steps. Well-planned reductive and/or oxidative transformations and intramolecular cyclizations were performed on a pivotal common precursor to accomplish collective first total synthesis of titled natural products and proposed Claulamine E. Burgess reagent induced formation of kinetically controlled product Claulamine A, and intramolecular cyclizations to form bicyclic claulansine A were the key reactions. An alternatively attempted synthesis failed to provide the structural isomer of proposed Claulamine E.